CRITICAL DISCOURSE ANALYSIS OF THE SHORT FICTION “MAGIC” BASED ON NORMAN FAIRCLOUGH’S APPROACH - Patricia Natasya Rhea Sudarna; Christina Atika Yulina (Universitas Suryakancana, 2021)
In the discussion about social injustice, inequality becomes a core issue. It is proven by inequality themed short stories which are still relevant nowadays although they were written decades ago. In this paper we analyse the 1928’s short story Magic written by Katherine Anne Porter under Fairclough's (1922) critical discourse analysis. It aims at finding social wrong—especially inequality issues in the short story and finding possible ways to solve the social wrong.The analysis will be done in the framework of Fairclough’s critical discourse methods which divides the discourse into three dimensions, i.e. linguistic description of the language text, interpretation of the relationship between the discursive processes and the text, and explanation of the relationship between the discursive processes and social processes (Fairclough, 1995). To describe the linguistic aspect of the text, appraisal theory is used as the approach to support the process of analyzing the linguistic elements that create the discourse. Thus, the analysis will link the linguistic and social contexts of the discourse. The results show that there are some social wrongs happen in the story. It is also shown through judgement, affect, and appreciation.